Parent-adolescent discussion on sexual and reproductive health issues and its associated factors among parents in Sawla town, Gofa zone, Ethiopia - Nigatu Teferi Malango; Tadele Yohannes Hegena; Netsanet Abera Assefa (BMC, 2022)
Plain English summary The health threats for adolescents today are predominantly behavioral rather than biomedical and more of today's adolescents are involved in health behavior with the potential for serious consequences. In most cultures, parents and family members are an influential source of knowledge, beliefs, attitudes, and values for children and youth. Open parent-adolescent discussion on sexual and reproductive health (SRH) issues often leads to increased awareness on reproductive health matters and reduces risky behaviors among adolescents and also is the base to reduce bad reproductive health outcomes. This study provides an overview of parent-adolescent discussion on SRH issues among parents in Sawla town in Southern Ethiopia. We found that only about one-fourth (25.7%) of the parents discuss at least two components of SRH issues with their children in the last 6 months prior to the study. Educational status, average monthly income, knowledge, and attitude on SRH issues were major factors for these disparities. Knowing the level of parent-adolescent discussion on SRH issues with their children and factors affecting the discussion may help concerned bodies to design Continuous capacity building and life skill training programs on SRH issues for parents and adolescents.